2020
DOI: 10.3390/foods9121826
|View full text |Cite
|
Sign up to set email alerts
|

Potentiality of Self-Cloned Lactobacillus plantarum Taj-Apis362 for Enhancing GABA Production in Yogurt under Glucose Induction: Optimization and Its Cardiovascular Effect on Spontaneous Hypertensive Rats

Abstract: The current study evaluated the γ-aminobutyric acid (GABA) producing ability from three novel strains of lactic acid bacteria (L. plantarum Taj-Apis362, assigned as UPMC90, UPMC91, and UPMC1065) co-cultured with starter culture in a yogurt. A combination of UPMC90 + UPMC91 with starter culture symbiotically revealed the most prominent GABA-producing effect. Response surface methodology revealed the optimized fermentation conditions at 39.0 °C, 7.25 h, and 11.5 mM glutamate substrate concentration to produce GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Our work identi es the lowest amount of glutamate (11.5 mM) as the effective concentration to foster optimum GABA production, as compared to previous works which reported glutamate usage of 32 mM in fermented palm date residue 15 and 80 mM in fermented milk 18 . This proves the e cient conversion of glutamate to GABA in yogurt fermented by UPMC90 and UPMC91 LAB strains under pre-de ned optimum conditions 19 .…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Our work identi es the lowest amount of glutamate (11.5 mM) as the effective concentration to foster optimum GABA production, as compared to previous works which reported glutamate usage of 32 mM in fermented palm date residue 15 and 80 mM in fermented milk 18 . This proves the e cient conversion of glutamate to GABA in yogurt fermented by UPMC90 and UPMC91 LAB strains under pre-de ned optimum conditions 19 .…”
Section: Resultsmentioning
confidence: 58%
“…Brie y, the yogurt samples were prepared by coinoculating starter culture and GABA-producing LAB strains (having viable count of 10 6 CFU/g) simultaneously at a ratio of 2:1 w/w, into fresh sterilised reconstituted skim milk. A total of 11.5 mM of glutamate was added and fermentation was allowed for 7.25 h at 39°C, which were the optimum conditions obtained from previous work 19 . Upon completion, samples were rapidly cooled in an ice bath to stop further fermentation and stored at 2-4°C until further analysis.…”
Section: Addition Of Sugars and Prebiotics Into Yogurtmentioning
confidence: 99%
“…In the present study, when the MRS broth contained 25 g/L of glucose, L. plantarum K16 synthetised the great concentration of 2115.7 mg/L of GABA. Furthermore, Hussin et al 69 reported the highest GABA synthesis by L. plantarum Taj-Apis362 using 20 g/L of glucose. However, L. plantarum EJ2014 only required 10 g/L of glucose to yield 19.8 g/L of GABA 70 and L. plantarum KCTC3103 showed the maximum GABA production (670 mg/L) using 5 g/L of glucose 71 .…”
Section: Discussionmentioning
confidence: 99%
“…By stimulating GABA A and GABA B receptors in nerve cells, GABA could promote vasodilation and lower blood pressure . Several studies found that GABA could not only significantly reduce blood pressure in rats with spontaneous hypertension, but also smooth blood pressure fluctuations, regulate heart rate, improve arterial baroreceptor reflex function, and protect cardiovascular tissue in rats. Moreover, Inoue et al also conducted a clinical study on the effects of GABA-containing fermented dairy products in patients with mild hypertension. It was found that the blood pressure remained low during the consumption of GABA-containing dairy products, while the blood chemistry variables, body weight, heart rate, and urinalysis results (glucosuria and proteinuria) did not show significant changes .…”
Section: Physiological Functions Of Gabamentioning
confidence: 99%